Radiographic and Endoscopic Features of Pancreaticoduodenal Malakoplakia. Issue 3 (March 2020) - Hubbard, Lauren; Iriana, Sentia; Carey, Adrienne; Odrobina, Robert; Sossenheimer, Michael; Rogers, Douglas
Abstract : Abstract: Malakoplakia is a rare, granulomatous disorder that is typically triggered by infections in immunocompromised patients. Although it most commonly affects the urinary tract, cases may occasionally occur in the gastrointestinal tract. There are case reports of malakoplakia of the pancreas with associated pathologic description, but none with detailed imaging and endoscopic findings. In addition, description of magnetic resonance imaging characteristics of mass-forming malakoplakia in the literature is sparse. We present a case of pancreaticoduodenal malakoplakia in an immunocompromised patient, including detailed description of magnetic resonance imaging, computed tomography, and endoscopic findings with radiology-pathology correlation. Classic pathologic features of malakoplakia (eg, hypercellularity, inflammation, and mineralization of Michaelis-Gutmann bodies) lead to specific features on imaging, such as marked diffusion restriction, heterogeneous enhancement, calcification, and increased attenuation on nonenhanced computed tomography. These features may help differentiate malakoplakia from other more common lesions that occur in this location, especially if present in an immunocompromised patient.